2016
DOI: 10.1002/alr.21826
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary management of chronic rhinosinusitis with nasal polyposis in aspirin‐exacerbated respiratory disease: an evidence‐based review with recommendations

Abstract: Background Chronic rhinosinusitis (CRS) in aspirin exacerbated respiratory disease (AERD) represents a recalcitrant form of sinonasal inflammation for which a multidisciplinary consensus on patient management has not been reached. Several medical interventions have been investigated, but a formal comprehensive evaluation of the evidence has never been performed. The purpose of this article is to provide an evidence-based approach for the multidisciplinary management of CRS in AERD. Methods A systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 99 publications
1
39
0
Order By: Relevance
“…Despite the significant importance of disturbances in the metabolism of arachidonic acid leading to the overproduction of proinflammatory CysLTs, drugs blocking receptor or leukotriene C4 synthase (LTC4S) are not recommended [1]. This is in contradiction with reports from the literature [3, 6, 8, 12, 16]. The last update of the ARIA document (Allergic Rhinitis and its Impact on Asthma) from 2016 allows to use antileukotrienes (LTRAs) as a supplement to therapy, especially in patients with asthma, in the case of seasonal allergic rhinitis [22].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the significant importance of disturbances in the metabolism of arachidonic acid leading to the overproduction of proinflammatory CysLTs, drugs blocking receptor or leukotriene C4 synthase (LTC4S) are not recommended [1]. This is in contradiction with reports from the literature [3, 6, 8, 12, 16]. The last update of the ARIA document (Allergic Rhinitis and its Impact on Asthma) from 2016 allows to use antileukotrienes (LTRAs) as a supplement to therapy, especially in patients with asthma, in the case of seasonal allergic rhinitis [22].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of the disease has not been explained. It is often associated with disruption of the arachidonic acid metabolic pathway and overproduction of leukotrienes [8, 9]. Feng et al [10] have found that in patients with NSAID-exacerbated respiratory disease (NERD) eosinophils have a greater capacity to produce and secrete prostaglandins D 2 after aspirin stimulation compared to healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations